Network Sovereignty : Building the Internet across Indian Country - Duarte, Marisa Elena (Book collections on Project MUSE., 2017)
"The histories of information and communication technologies (ICTs) are intertwined with U.S. histories of colonization, and the sovereignty and self-determination of Native peoples. This book examines case studies of tribal governments building out broadband infrastructures--the infrastructures that undergird uses of ICTs such as mobile phones, computers, databases, and streaming radio--to reveal how the processes of network design and deployment embed these information and communication infrastructures within the ongoing exercise of tribal sovereignty in the U.S."--